Homochiral 3D coordination polymer with unprecedented three-directional helical topology from achiral precursor: synthesis, crystal structure, and luminescence properties of uranyl succinate metal–organic framework1. Issue 31 (21st August 2015) - Wang, Juan; Wei, Zhen; Guo, Fengwan; Li, Chenyang; Zhu, Pengfei; Zhu, Wenhua
<x xml:space="preserve">Abstract</x> Synthesis, crystal structure and luminescence properties of uranyl chiral coordination polymers from achiral ligands.